2020
DOI: 10.21608/agro.2020.30089.1226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Monogenic Lines of Wheat Leaf Rust Caused by Puccinia triticina

Abstract: W HEAT leaf rust, caused by the fungus Puccinia triticina Eriks., is a destructive disease found throughout common wheat production areas worldwide. Fifty wheat leaf rust monogenic lines were tested with five of Puccinia triticina pathotypes, i.e. BJPPQ, LQFDS, PHFPG, PTPDN, TRFDJ at four stable temperatures (30 0 C, 25 0 C, 20 0 C and 15 0 C). The wheat monogenic lines viz. Lr 16, Lr 17 and Lr 23 were more resistant at 25 0 C, while these genes were found susceptible at 15 0 C, 20 0 C and 30 0 C to all tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Unfortunately, we could not include this gene in our evaluation due to the lack in seeds of its line. However, previous study reported the susceptibility of this gene against the Egyptian races of LR ( El-Orabey et al, 2020 ). Therefore, we can confirm that chromosomes 6D carries unknown resistant genes which provides broad-spectrum resistance to almost all Pt Egyptian races.…”
Section: Discussionmentioning
confidence: 91%
“…Unfortunately, we could not include this gene in our evaluation due to the lack in seeds of its line. However, previous study reported the susceptibility of this gene against the Egyptian races of LR ( El-Orabey et al, 2020 ). Therefore, we can confirm that chromosomes 6D carries unknown resistant genes which provides broad-spectrum resistance to almost all Pt Egyptian races.…”
Section: Discussionmentioning
confidence: 91%
“…First, it was shown by El‐Orabey et al. (2020) that expression frequencies for several Lr genes often depend on temperature. Secondly, and more importantly, a population of P. triticina from a susceptible variety in a given location is expected to be very similar to the corresponding natural population in that location.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of leaf rust resistance genes is known to be temperature dependent (Dyck & Johnson, 1983). For example, in Egypt, lines with genes Lr11 , Lr12 , Lr13 , Lr14a , Lr18 , Lr47 , Lr50 and Lr68 were susceptible at 25–30°C and resistant at 15 and 20°C, while other Lr genes were equally stable at all temperatures (El‐Orabey et al., 2020). Adult‐plant resistance (APR) genes are most often temperature sensitive (Kaul & Shaner, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of wheat, it is known that some resistance genes against the most important rusts (leaf rust, yellow rust and stem rust) are influenced by temperature, being effective only at warm environmental conditions 41 43 . As a consequence, the deployment of this kind of genes requires experiments with specific conditions of increasing temperature in wheat-rust interactions for their identification 44 46 , which would become complex in future breeding studies if weather conditions become warmer.…”
Section: Introductionmentioning
confidence: 99%